Analisis Komparatif Transformasi Kebijakan Pemotongan PPh Pasal 21 Antara PER-16/PJ/2016 dan PP No. 58 Tahun 2023 - Sina Alviani; Khoirina Farina (AKUNTANSI 45, 2025)
This study aims to examine the differences in the calculation of Income Tax (Article 21) based on the provisions stipulated in PER-16/PJ/2016 and Government Regulation Number 58 of 2023. Income Tax Article 21 is a tax on income imposed on domestic individual taxpayers in connection with with jobs, services, or activities. PER-16/PJ/2016 provides guidance for calculating PPh Article 21 using a certain method that has been used for several years, but with the presence of PP 58/2023, there has been a change in the calculation of this tax. This research uses a qualitative descriptive method with comparative analysis to see the main differences in these regulations. The main focus of this research is changes in provisions that impact employee tax calculations, including differences in tax rates and calculation methods. This study also highlights changes in regulations regarding companies that use the net method in calculating taxes, as well as how these changes affect the company’s tax obligations in paying PPh 21 employees. The research results show that there are differences between the two regulations, both in terms of calculation procedures and financial impacts for the company. This change requires adaptation by companies in managing employee taxes to remain compliant with applicable regulations.